Risk factors of ICU or high dependency requirements amongst hospitalized pediatric pertussis cases: A 10 year retrospective series, Singapore. Issue 47 (7th November 2017) - Chong, Chia-Yin; Yung, Chee-Fu; Tan, Natalie Woon-Hui; Acharyya, Sanchalika; Thoon, Koh-Cheng
Abstract: Introduction: Pertussis causes the highest complication rates and deaths in the infant group. Our study explored risk factors for ICU/high dependency (HD) admissions and intubation/non-invasive ventilation (NIV). Methods: A retrospective review of pertussis admissions over 10 years from 2007 to 2016 was done at KK Women's and Children's Hospital, Singapore. To understand risk factors for severe pertussis infection, we compared cases requiring ICU/HD care with controls admitted to the general ward. Risk factors for intubation/NIV were also studied. Vaccine efficacy for protection against ICU/HD admission or intubation/NIV was also calculated. Results: There were 200 pertussis patients with a median age of 2.75 months. Sixty-one % were ≤3 months and 14.5% were <6 weeks old. Majority of patients (77%) had no prior pertussis vaccination. After removing 3 patients with missing vaccination records, 20 cases were compared with 177 controls. On univariate analysis, risk factors for ICU/HD admission comprised: Age ≤3 months, contact history, underlying co-morbidity, prematurity, absent DTaP vaccination, lymphocytosis, hyperleukocytosis (wbc ≥50 × 10 9 /L), thrombocytosis (platelet ≥500 × 10 9 /L), and pneumonia. Multivariate analysis revealed that age ≤3 months (OR 40, 95% CI 4.57–1111.11, p = .007), co-morbidity (OR 8.46 (95% CI 1.47–56.89, p = .019), pneumonia (OR 18.08, 95% CI 3.22–132.15, p = .002), white cell count (OR 1.07, 95% CI 1.01–1.14, p = .023) and cyanosis (OR 5.09, 95% CI 1.31–24.71, p = .026) were risk factors for ICU/HD admission. Prior DTaP vaccination had a vaccine effectiveness of 86.5% in preventing ICU/HD admission and 82.1% in preventing intubation/NIV. Conclusions: As the majority of pertussis patients were infants ≤3 months old who are at high risk for ICU/HD admission and intubation/NIV, prevention is key to reducing pertussis morbidity. Even though not statistically significant, DTaP vaccination had a role in preventing ICU/HD admission and intubation/NIV.